Pemberian Sanksi dan Efek Jera Pemberian Sanksi dan Efek Jera terhadap Negara yang Melanggar Hukum Humaniter Internasional - Nasution, Muhammad Mukmin Toat (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2025)
The provision of sanctions against countries that violate international humanitarian law is one of the mechanisms to enforce international norms. This sanction aims to create a deterrent effect, so that the country concerned does not repeat the violation. This study analyzes the various types of sanctions applied by the international community and their effectiveness in providing a deterrent effect. The methodology used is literature study and case analysis. The results of the study show that although sanctions can have a deterrent effect, their success is highly dependent on the political and economic context of the sanctioned country.